2018
DOI: 10.1155/2018/3250908
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Neuroprotective Properties of Eugenia dysenterica Leaves

Abstract: Eugenia dysenterica ex DC Mart. (Myrtaceae), popularly known as “cagaita,” is a Brazilian plant rich in polyphenols and other antioxidant compounds. Aiming to evaluate the potential use of cagaita in pathologies involving oxidative stress, such as neurodegenerative disorders, this study investigated its antioxidant potential and neuroprotective effect. Electrochemical approaches and aluminium-induced neurotoxicity were used to determine respectively in vitro and in vivo antioxidant properties of cagaita. Volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…Collectively, the findings of the current study fit within the modernized attempt of phytomedicine to explore the benefits of polyphenols in neurodegenerative diseases. Several polyphenol‐rich plants have been shown to protect the brain against oxidative stress in addition to other effects such as an anti‐Aβ fibrillation and microglial neuroprotective effects (Thomaz et al., ). Being a major subclass of polyphenols, flavonoids have demonstrated neuroprotective effects by increasing neuronal viability, reducing loss of dopaminergic neurons in the brain, having an anti‐amyloidogenic effect, and improving cognitive impairment (Chen, Wu, et al., ; Putteeraj, Lim, Teoh, & Yahaya, ).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the findings of the current study fit within the modernized attempt of phytomedicine to explore the benefits of polyphenols in neurodegenerative diseases. Several polyphenol‐rich plants have been shown to protect the brain against oxidative stress in addition to other effects such as an anti‐Aβ fibrillation and microglial neuroprotective effects (Thomaz et al., ). Being a major subclass of polyphenols, flavonoids have demonstrated neuroprotective effects by increasing neuronal viability, reducing loss of dopaminergic neurons in the brain, having an anti‐amyloidogenic effect, and improving cognitive impairment (Chen, Wu, et al., ; Putteeraj, Lim, Teoh, & Yahaya, ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to explore the physicochemical features of herbal preparations, all samples were subjected to voltammetric screenings, such as: Cyclic Voltammetry (CV), Square Wave Voltammetry (SWV) and Differential Pulse Voltammetry (DPV) (Thomaz et al, 2018a(Thomaz et al, , 2018b. All experiments were conducted using potentiostate/galvanostate PGSTAT ® model 204 coupled to FRA32M module (Metrohm) and integrated to NOVA 2.1 ® software.…”
Section: Electrochemical Determination Of Redox Kinetics and Thermodymentioning
confidence: 99%
“…The antioxidant capacity of phytochemicals is a well-known feature, and its mechanisms are nonetheless explored in many cosmetical and nutraceutical products [9,10]. Given the relationship between the chemical structure and physicochemical features such as antioxidant capacity, many compounds bearing similar structural characteristics also showcase similar thermodynamic feasibility to undergo oxidation [11][12][13]. Amongst these compounds are polyphenols, whose oxidation mechanism often contemplates reversibility, as showcased with ocatechol as instance in (Figure 2).…”
Section: The Physicochemical Aspects Of Phytochemical Antioxidantsmentioning
confidence: 99%
“…Considering that exogenous antioxidants such as plant secondary metabolites may restitute and preserve the activity of the endogenous antioxidant arsenal, as well as scavenge ROS, it can be suggested that these phytochemicals may play a part in aiding brain tissue to keep its integrity. Notwithstanding, several reports showcased the effectiveness of plant-based antioxidants such as polyphenols in mopping up free radicals and hindering lipid peroxidation, as well as preserving nervous functions such as memory, mobility, balance and other cognitive features [11,12].…”
Section: How Can Secondary Metabolites Hinder Brain Tissue Damage Upomentioning
confidence: 99%
See 1 more Smart Citation